Survey of the fecal microbiota of indigenous small ruminants living in different areas of Guizhou - Guo, Wei; Liu, Tingmei; Wang, Weiwei; Yu, Yinshu; Neves, André Luis Alves; Zhou, Mi; Chen, Xiang (Frontiers in Microbiology, 2024)
Introduction Gut microbiota are associated with the health and performance of ruminant species, and they are affected by altitude, host genetics, and sex. However, there has been little research on comparing the fecal microbiota of indigenous small ruminants such as sheep and goats in Guizhou province, China. In the present study, we revealed the effect of altitude, genetics, and sex on fecal microbiota profiles and enterotypes in indigenous small ruminants of Guizhou province, China. Methods Fecal samples were collected from Hei and Qianbei Ma goats and Weining sheep in the Chinese province of Guizhou. 16S rRNA gene sequencing targeting the V3–V4 region was performed using the Illumina MiSeq platform. Sequences were processed using QIIME2, and the qualified sequences were processed using the plugin DADA2 to generate amplicon sequence variants (ASVs). The statistical analysis was performed using R studio. Results The fecal microbial profile was found to vary by herd (influenced by genetics/altitude) and sex. All samples were categorized into two enterotypes. The first enterotype is dominated by UCG-005, and the second enterotype is dominated by the Christensenellaceae_R-7_group, which may be highly driven by the host's genetics (breed). The predicted functional profiles of the fecal microbiota were also assigned to two clusters that corresponded exactly to the enterotypes. Cluster 1 of the functional profiling was characterized by biosynthesis pathways, and cluster 2 was characterized by energy metabolism pathways. Discussion Our findings may provide new insights into the fecal microbial community and enterotypes in small ruminants by herds, offering clues for understanding the mechanisms by which the fecal microbiota contribute to divergent host phenotypes in indigenous small ruminants in Guizhou.